(untitled) (Práxis Educativa, 2014)
Can education, in the current status of the capitalist society, contribute to human emancipation? The aim of this paper is to defend the idea that generally it is not possible to organize education in its form and its content in order to contribute to the construction of a fully emancipated society. However, to the extent that capitalist society presents, in essence, a contradiction between capital and labor, we believe that it is possible to hold, within its own educational dimension, activities that contribute to the radical transformation of the world and to the construction of a form of sociability that goes beyond and is superior to capitalism. Keywords: Human emancipation. Education. Educational activities.